MANAGEMENT OF ASTHI-MAJJA GATA VATA WSR INTER VERTIBRAL DISC PROLAPSE (IVDP) WITH SAGHRITHA KSHEERA BASTI – A CONCEPTUAL STUDY - K, *Rajesh; Khader, Abdul (AYUSHDHARA, 2016)
Lumbago is the third most common symptom presented to general practitioners. Worldwide, 37% of low back pain was deemed attributable to occupational risk factor. Dhatus like Asthi and Majja in Prakrutha avastha does Dharana and Poorana to body and in Vikrutha avastha produce leads to Asthi shoola, Asthi kshaya, Asthi shoonyataetc. Gatatva (movement/passage) is a phenomenon which is used for explaining about the Samprapthi that results in Dhatu kshaya (diminished). The Lakshana of Asthi Majja gata vata is Bhedo asthi parvani (cracking of bones and joints) Sandhi shoola (piercing pain in the joints), Mamsa bala kshaya (diminution of muscle tissues), Aswapna (insomnia) Santata ruja (constant pain). The disease that which comes under these are Kati graha (low back stiffness), Gridhrasi (sciatica), etc Inter vertebral prolapsed disc IVPD is a pathology condition which has symptom of lumbago, caused due to strenuous activities, it has 4 stages and once pathology crosses 2nd stage condition cannot be reversed. It starts from severe low back pain, which may be localized then radiates and progresses towards producing towards symptoms like numbness, reduced strength etc. Acharaya charaka while explaining about treatment for Asthimajja gata vata, emphasizes to consider both Asthi and Majja for treating through Snehan in both Bahya (externally) and Abhyantara (internally). While explaining about Asthi pradoshaja vikaara he explains to adopt treatment of Panchakarma in which he gives Importance to Basti, containing Ghritha and Ksheera as main Dravya.